2019
DOI: 10.1111/jpn.13110
|View full text |Cite
|
Sign up to set email alerts
|

Dietaryl‐arginine supplementation influences growth performance and B‐cell secretion of immunoglobulin in broiler chickens

Abstract: Our previous study has shown that high levels of l‐arginine (ARG) have reduced serum and mucosal antibody concentrations. In order to provide a better understanding in the application of ARG supplementation in the poultry industry, the study was conducted to investigate the effect of high levels of ARG on performance and B‐cell secretion of immunoglobulin M (IgM) and IgG development in broiler chickens. A total of 192 1‐day‐old male Arbor Acres Plus broilers were randomly allocated into 4 groups (8 replicates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 50 publications
4
11
0
Order By: Relevance
“…Arginine is a hub precursor for the synthesis of various important metabolic molecules, including NO and polyamines, exerting regulatory roles in the host's metabolic processes (Flynn et al, 2002). Thus, it has been used to improve meat production in meat-producing animals (Hu et al, 2017;Liu et al, 2019). Conversely, gut microbiota is involved in aromatic amino acids (tryptophan, tyrosine, and phenylalanine) metabolism has been linked to chronic low-grade inflammation and metabolic disorders, which may hinder development and growth of animals (Wang et al, 2011;Agus et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Arginine is a hub precursor for the synthesis of various important metabolic molecules, including NO and polyamines, exerting regulatory roles in the host's metabolic processes (Flynn et al, 2002). Thus, it has been used to improve meat production in meat-producing animals (Hu et al, 2017;Liu et al, 2019). Conversely, gut microbiota is involved in aromatic amino acids (tryptophan, tyrosine, and phenylalanine) metabolism has been linked to chronic low-grade inflammation and metabolic disorders, which may hinder development and growth of animals (Wang et al, 2011;Agus et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In another study Emadi et al (2010) supported the previous findings and reported that FCR improved as the arginine level was reduced from 3.35 to 1.10%. Similarly, Liu et al (2019) reported that FCR was optimum when 14.7 g/kg arginine was supplemented in the broiler diet. Ebrahimi et al (2014) reported that as the arginine supplementation in the broiler diet was increased from 100% of requirement to 183%, the FCR improved significantly.…”
Section: Effect Of Arginine On the Growth Performance Of Broilersmentioning
confidence: 89%
“…Similarly, Jahanian and Khalifeh-Gholi (2018) reported that the relative weight of bursa of Fabricius and spleen were more in birds fed 100% level of arginine. Likewise, Liu et al (2019) reported that when arginine supplementation was increased from 9.8 to 23.4 g/kg, serum immunoglobulin's (IgM and IgG) were increased. Kidd et al (2001) reported that when dietary arginine levels were decreased the antibody titer of the birds reduced significantly.…”
Section: Effect Of Arginine On the Growth Performance Of Broilersmentioning
confidence: 97%
“…Cytokines IFN-α/γ Immunoglobulin G [33] Antibody titer [23] B cells [34] Lymphocyte proliferation Basophil hypersensitivity [35] Cytokines IFN-α/γ Immunoglobulin G [36] Lymphocyte and antibody [37] Immunoglobulin A and M Cytokine INF-α Lymphocytes proliferation [38] T cells and B cells Lymphocytes CD4+ and CD8+ [39] Bacteria Immunoglobulin M [40] Immunoglobulin A regulation [41] Parasite Immunoglobulin A production [42] Pig Bacteria Immunoglobulin A CD8+ and CD4+ T cells production [43]…”
Section: Virusmentioning
confidence: 99%